Prevalência de co-infecção pelos vírus linfotrópico de células T humanas do adulto – HTLV e vírus da imunodeficência adquirida – HIV, no Ceará - Bezerra, Leila Maria Machado (2003)
Several studies carried out in Brazil have shown a serum-prevalence rate of HIV / HTLV (Human Immunodeficiency - virus / Human T-Lymphotropic virus) co-infection of 0.58% to 11.4% among specific groups of individuals. Based on previous data, the State of Ceará is considered an area of low HTLV prevalence in the northeastern Brasil. This study evaluated the clinical and epidemiological aspects of the HIV / HTLV co-infection in a reference hospital for the treatment of HIV infected patients in Ceará. A descriptive, cross sectional study was performed, in the period of May of 2001 to October of 2002. Blood samples were randomly collected from 420 HIV-positive patients, through Elisa and Western Blot tests, that later were serologically tested for HTLV-I/II in the Hematological Center of Ceará - HEMOCE. Interviews were done in 337 patients and 165 files were searched for socio-economic, risk factors for HTLV, sexual practice and clinical aspects. The results confirmed a general seroprevalence value of 0.95%, distributed as 0.23% of HIV-HTLV-I and 0.47% of HIV-HTLV-II, followed by one (0.23%) sample of undetermined serology. Concomitant infection was not evidenced by the viruses HTLV-I and HTLV-II. The population studied was more frequently 30 to 39 years old, had predominantly lower income (67.6%) and educational (44.8%) levels and were heterosexual mainly (67,8%). In 119 patients evaluated, 105 (88.2%) complained of HIV-related diseases, 14 (11.8%) were asymptomatic and 111 (93.3%) were diagnosed with AIDS. An elevated percentage was breast fed (38.5%), few had had tattoos (12.2%), and also did receive blood products (15,9%). The scarce use of intravenous drugs (4.8%), the few numbers of black individuals (5.6%) and higher numbers of heterosexuals (67.8%), were pointed as possible reasons for the low HTLV prevalence found in this research.